Assessment of yield loss of mustard due to Alternaria leaf blight in Gangetic plains of West Bengal - SRIKANTA DAS, SUNITA MAHAPATRA* and (Indian Phytopathology, 2017)
Alternaria leaf blight of mustard caused by Alternaria brassicae and Alternaria brassicicola occur severely in different districts of West Bengal. A mustard variety ‘Binoy’ was used to assess the effect of iprodion. Three sprays of Iprodion @0.2% at 10 days interval beginning from 45 days after sowing resulted in lowest alternaria blight under moderate disease pressure and four sprays for high disease pressure resulted in highest seed yield and cost benefit ratio of 5.19 and 4.61 respectively for commercial seed and 8.43 and 7.48 for certified seed. Highest avoidable losses of seed yield and 1000 seed weight due to the alternaria blight infection were 27.24% and 5.98% for three sprays and 30.71% and 0.74% for four sprays respectively. The results indicated that three sprays of Iprodion (0.2%) resulted in minimum disease severity and maximum profit whereas under high disease pressure four sprays were essential for minimum disease severity and maximum profit in Indo-Gangetic plains of West Bengal.